Archetype Analysis Of The Main Characters In The Three Stooges - Syamsul Bahri; Raja Sungai Simbolon; Anastasya Dwika Simanjuntak; Steven Nikson Sitanggang (FKIP, Universitas Palangka Raya, 2024)
This study delves into the portrayal of character archetypes in